Lean manufacturing is the financial performance and sustainable finances problems solution? - Maldonado-Guzmán, Gonzalo (2023)
Lean manufacturing is gaining popularity among scientific, academic, and business communities; and is considered a valid strategy to generate financial performance and more sustainable finance. However, little is known about the influence of lean manufacturing on financial performance and sustainable finance of firms in the automotive industry. This study explores the relationship between lean manufacturing, financial performance and sustainable finance. The data was obtained from a self-administered questionnaire distributed to 460 Mexican firms that operate in the automotive industry. The results of the structural equation model (partial least squares) suggest that lean manufacturing have a positive and significant influence on both financial performance and sustainable finance.